Diagnóstico do sistema de abastecimento de água do campus da Fundação Universidade Federal de Mato Grosso em Cuiabá como subsídio a uma proposta de uso racional de água - Silva, José Álvaro da (2015)
The aim of this study is to develop a diagnosis of the water supply system of the UFMT campus in Cuiabá to allow the definition of a new project based on the concept of rational use of water, using technological actions and conservation measures. The need to save water and preserve water resources for future generations has become a global concern. Following the recommendation of the Ministry of Education and the Environment, the Campus Sustainable Logistics Plan (PLS) was prepared, guided by the Regulatory Instruction No. 10/2012 of the Ministry of Planning, Budget and Management and by the Green Manual of Education for the IFEs (Federal Institutes of Education). The water supply system of the campus is inserted in this context. The bibliographic research shows that the concern about the conscious use of water, reducing losses and consumption is the main action to expand the capacity of a water supply system and ensure the preservation of water resources. The methodology used in this work consists of the elaboration of a diagnosis of the system, which includes the survey of primary and secondary data, and a bibliographic research on the use of regulatory parts of flow and rain water utilization to support the adoption of conservation measures and the recommendations of the work. Data were organized, analyzed and evaluated to enable the preparation of a new project for the campus water supply system and possible future scenarios that may occur. The diagnosis conducted revealed a system with a decentralized model, with two water supply sources in which one is a superficial source (Supplier) and another one underground through four deep wells. The distribution network has various types of materials, with the predominance of PVC with 68% and asbestos cement with 23%, this one with outdated useful life. The network also shows total lack of technical records, which has led to constant disruptions and interruptions in the water supply. The reserve capacity installed is of 1988.20 cubic meters and the per capita consumption found is 60.72 l / hab.dia. For the new project it was proposed: the maintenance of two sources of water supply; the construction of two main reservoirs for distribution; the separation of drinking and non-drinking water consumption through independent networks installation of macro and micro gauge to allow the water balance of the system. As a recommendation, some conservation measures were proposed such as an environmental education program, a manual for the operation and maintenance of the system, the use of rainwater for toilet flushing and urinals, to reuse water dropped from distillers, among others. We conclude that, in addition to technological actions and conservation measures recommended, it is also necessary to implement an Operational Control Center to monitor and control consumption, and to rewire electrical installations and automation of all existing individual settlements.